Trophic States and Fishery Potential of Tidal Lakes, Lake Siombak, Medan, Indonesia - Ahmad Muhtadi; Rusdi Leidonald; Ahyar Pulungan; Nur Rohim; Qadar Hasani (Indonesian Society of Limnology, 2023)
Siombak Lake is one of the tropical coastal lakes in Indonesia, which is unique and distinctive because it is directly influenced by the tidal dynamics of the Malacca Strait (7 km away) through the Belawan estuary. Therefore, Lake Siombak is brackish in its extensive pool. This lake functions as a water catchment, fishing area, and recreation area. This research aims to determine the fertility level and fisheries potential of Lake Siombak waters. The research was conducted from September 2018 to August 2019, but chlorophyll data was only taken for 4 months, namely November 2018, February, June, and August 2019. Water samples were taken during high tide and low tide conditions. Data taken to determine water fertility includes water brightness, phosphate concentration, and chlorophyll a. The fertility of lake waters is determined using various methods, namely the trophic State Index (TSI) method, Trix method, Trophic State Index Lamp (TSI Lamp), and Tropical Level Index (TLI). The brightness of Lake Siombak's waters ranges from 0.6–1.1 m. Phosphate concentrations ranged from 0.05-14.16 mg/L. The chlorophyll content in Siombak Lake ranges from 0.019 – 0.445 mg/m3. The fertility level of Lake Siombak waters is eutrophic-hypereutrophic with a TSI value of 52.0-71.9; Trix index of 2.8-4.9; TSI lamp is 53.7-68.4; and TLI of 4.76-6.32. Spatially, the most fertile lake location is Station 1 (southern region), and temporally the dry season (February) is more fertile than the rainy season (November). The fisheries potential in Lake Siombak ranges from 320 – 773 kg/ha/month. The potential for fisheries production in Lake Siombak is highest in March.